Impact of structural uncertainties on the buckling strength of cylindrical GLARE panels subjected to uniform compression - Kalfountzos Costas (EDP Sciences, 2021)
The objective of this article is the investigation of the elastic buckling strength of cylindrical simply supported GLARE (GLAss REinforced) panels subjected to axial compression using probabilistic analysis methods, so that the effect of uncertainties associated with material properties and dimensions of the panels on their elastic buckling load can be evaluated. The mechanical properties of aluminum along with the dimensions of aluminum and unidirectional (UD) glass-epoxy layers are considered to be random input variables whereas the critical buckling load is defined as a random output parameter. The employed eigenvalue buckling analysis and the probabilistic finite element analysis were carried out with ANSYS software. The Probabilistic Design System (PDS), along with the Monte Carlo Simulation and the Latin Hypercube Sampling method were used for the calculations. It is found that the thickness of aluminum layers has the strongest effect on the buckling strength, among the considered random input variables. It is also demonstrated that there is a considerable probability for the buckling load of GLARE panels to be overestimated when a deterministic analysis is conducted.